Looking for consensus? civil society, social movements and crises for public management - Diamond, John, 1954-; Liddle, Joyce, 1952- (Critical perspectives on international public sector management ;, 2013)
This volume reflects on the global dimension of the 2008 banking and financial crisis and the point to a bigger and deeper crisis of authority and legitimacy for public managers. The peak of the crisis might be passing but the crisis for civil society and civic institutions of governance and leadership is far from over. The long term implications of these crises for governance, political and civic institutions are hard to be precise about. However, we can observe how across a number of nation states and supra national relationships (from the European Union to the IMF) are institutions and those who lead, manage or hold them to account in crisis too. The broad group of scholars and academics examine key conceptual and theoretical ideas in contemporary international public management and explore: What are the implications of these developments for city managers and local political leaders (from elected mayors to NGO leaders and activists) ? Is coalition and consensus building possible in a time of uncertainty and change? And, finally, what are the implications for those who seek to manage or administer public services in this time of crisis?